Accounting for Wage Inequality in India - PUJA VASUDEVA DUTTA (PRUS Working Paper no. 29, 2005)
This paper investigates the evolution and structure of wage inequality among adult male workers engaged in regular and casual wage employment in India during a period of radical economic change. The analysis exploits data from nationally representative employment surveys and uses decomposition techniques to examine the role played by educational achievement and industry affiliation. This paper finds that there are striking differences for the two groups of workers. Wage inequality rose between 1983 and 1999 among regular workers but fell among casual workers. While human capital (as embodied in age and education) is one of the major factors explaining both the level of and change in regular wage inequality, geographic location is the key determinant of casual wage inequality. Industry affiliation plays an equally important role for both sets of workers. These are also consistently the most important contributors to changes in inequality though the directional effects differ among the different sets of workers..